La autoevaluación del desempeño laboral y la calidad de servicios que ofrece la constructora obremin cía. Ltda. De la ciudad de Loja, periodo abril- julio del 2011 - Zaquinaula Tamay, Mirian Margarita (2015)
Companies today must keep pace with the constantly changing environmental demands; this implies that the quality of a service depends, first order of human talent competition that he plays or works. It is for this reason that arose "THE SELF JOB PERFORMANCE AND QUALITY OF SERVICES OFFERED BY THE BUILDER OBREMIN CIA. LTDA. LOJA CITY, April - July 2011 ", as a mechanism for evaluation, it was necessary to make a diagnosis of the current situation, gathering information by conducting surveys of the construction staff, identification of internal users and external to meet their expectations and demands and thus generate strategies according to the reality found and projecting the company for the future. Constraints were ordered held by the builder, to enhance each of them, with the help of tools like the SWOT matrix to determine Strengths, Opportunities, Weaknesses and Threats, working groups were held with staff to determine the mission and vision institutions in order to develop projects and programs to operationalize the strategies and finally put forward a proposal that will serve as the builder horizon.